2000
DOI: 10.1063/1.481942
|View full text |Cite
|
Sign up to set email alerts
|

Dissociative photoionization of CF4 from 23 to 120 eV

Abstract: Using synchrotron radiation as a continuum light source, dissociative photoionization of CF 4 has been studied in the photon-energy region of 23-120 eV. Ion branching ratios were obtained by analyzing time-of-flight mass spectra and were converted to the absolute partial cross sections for the production of singly charged CF 3 ϩ , CF 2 ϩ , CF ϩ , F ϩ , and C ϩ ions, as well as doubly charged CF 3 2ϩ and CF 2 2ϩ ions by using the reported total absorption cross sections of CF 4 . Ion branching ratios were diffe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
13
0

Year Published

2002
2002
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 50 publications
3
13
0
Order By: Relevance
“…In addition, a weak contribution of the (4a 1 ) −1 state is observed. Comparing the earlier studies for the formation of the CF 3 + ion, this is in agreement with TPEPICO studies [4,20,26] while the PEPICO [24] and TPEFCO [? ] studies did not identify the weak contribution of the (4a 1 ) −1 orbital.…”
Section: Fragment Ion Time Of Flight (Tof) Spectrum Of Cfsupporting
confidence: 77%
See 2 more Smart Citations
“…In addition, a weak contribution of the (4a 1 ) −1 state is observed. Comparing the earlier studies for the formation of the CF 3 + ion, this is in agreement with TPEPICO studies [4,20,26] while the PEPICO [24] and TPEFCO [? ] studies did not identify the weak contribution of the (4a 1 ) −1 orbital.…”
Section: Fragment Ion Time Of Flight (Tof) Spectrum Of Cfsupporting
confidence: 77%
“…Masuoka and Kobayashi [20] also observed similar results but did not observe the small contribution of the 1e orbital. The electron impact dissociative ionization study [48], found appearance energy below 20 eV and concluded the contribution of the (1e) −1 state.…”
Section: Cf 2 +supporting
confidence: 69%
See 1 more Smart Citation
“…Statistical activated complex theories, namely, the quasiequilibrium theory of mass spectra of Rosenstock et al [9] can, in general, account reasonably well for PICSs in hydrocarbons [10,11], although performs poorly for highly fluorinated or PFC species. The poor performance for PFCs is due to a breakdown of the statistical approximation: Impulsive dissociation may occur directly from some excited states, and hence, fragment ions can exhibit high kinetic-energy release (KER) [12][13][14][15][16][17][18][19][20][21][22][23][24][25]. The inadequacy of statistical models for the PFCs means that accurate experimental characterization of PICSs for such species, in particular, for groups of related structures, is important both for gaining further insight into the fundamental dynamics of ionization and for aiding interpretation of mass spectra in analytical applications.…”
Section: Introductionmentioning
confidence: 99%
“…In the last few years modern experimental techniques such as double charge transfer spectroscopy [1][2][3], time-of-flight mass spectrometry [4], photoion and photoelectron coincidence spectroscopy [5][6][7] and threshold photoelectron coincidence (TPEsCO) [8] allowed for a detailed analysis of double ionization processes and a characterization of the resulting fragments. In these processes atoms, molecules or clusters are irradiated by photons of sufficient energy to produce at least two photoelectrons and dications that undergo fragmentation in most cases.…”
Section: Introductionmentioning
confidence: 99%